Pengaruh Mutasi Kerja dan Beban Kerja Terhadap Kinerja Pegawai - Anggriani Husain (Oikos Nomos: Jurnal Kajian Ekonomi dan Bisnis, 2022)
This study aims to find out to what extent: (1) the job transfer (X1) and workload (X2) simultaneously on the employee performance (Y) at the East Suwawa Subdistrict Office, and (2) the work mutations (X1) partially on the employee performance (Y) at the East Suwawa Subdistrict Office, (3) the effect of the workload (X2) partially on the employee performance (Y) at the East Suwawa Subdistrict Office. The method used in this research is a quantitative approach with a descriptive presentation. The population in this study consists of all employees of the East Suwawa Subdistrict Office, and the sample used in this study covers 30 respondents by using a random sampling technique. The data collection technique is through observation, interviews, and questionnaires distributed to respondents. The analysis method uses path analysis. The results of the study indicate that: (1) job transfer (X1) and workload (X2) simultaneously has a positive and significant effect on the employee performance (Y) at the East Suwawa Subdistrict Office, namely 0.904 or 90.4%, (2) job transfer (X1) partially has a positive and significant effect on the employee performance (Y) at the East Suwawa Subdistrict Office, which is 0.576 or 57.6%, and (3) workload (X2) partially has a positive and significant effect on the employee performance (Y) at the East Suwawa Subdistric Office, which is 0.388 or 38.8%.